359 Delayed Treatment of Ruptured Arteriovenous Malformations: Is It Ok to Wait?. (August 2016) - Beecher, Jeffrey S.; Vance, Awais; Lyon, Kristopher Allen; Ban, Vin Shen; McDougall, Cameron Michael; Whitworth, Louis A.; White, Jonathan A.; Samson, Duke S.; Batjer, H. Hunt; Welch, Babu Guai
Abstract : INTRODUCTION: Emergent surgery on a ruptured brain arteriovenous malformation (AVM) is indicated for a large hematoma in an acutely deteriorating patient. The majority of ruptured AVMs, however, present in clinically stable patients with neurological deficits. Controversy exists with respect to the timing of treatment for ruptured AVMs in these stable patients. This study aims to determine the safety of delaying AVM treatment in clinically stable patients by investigating the rate of rehemorrhage in a cohort of patients with ruptured brain AVMs. METHODS: Patients presenting to our institution from January 2000 to December 2015 with ruptured brain AVMs treated at least 4 weeks posthemorrhage were included in the analysis. Exclusion criteria were ruptured AVMs that required emergent surgery involving AVM resection, previous treatment at another institution, or subacute AVM treatment. The primary outcome measure was time from initial hemorrhage to rehemorrhage. Patient follow-up data were included up until the point of AVM treatment. RESULTS: Of the 103 ruptured AVMs (49 M:54 F) meeting inclusion criteria, the median time from rupture to treatment or rehemorrhage was 112 days (interquartile range [IQR]: 110). Six (5.8%) patients rehemorrhaged in a median of 248 days (IQR: 1331). Two of these patients rehemorrhaged on the same day of their index hemorrhage. The total at-risk period was 19 445 patient-days, yielding a rehemorrhage risk of 11.3% per patient-year, or 0.93% per patient-month. CONCLUSION: Our data support stabilizing a patient after the initial AVM rupture. It is safe to closely monitor the patient, initiate the rehabilitation process, and then, in a semielective manner, bring the patient back for treatment. Delaying intervention for 4 weeks after initial hemorrhage subjects the patient to a low (<1%) risk of rehemorrhage.